Kondisi Sosial Ekonomi Masyarakat Desa Wombo Kalonggo Kecamatan Tanantovea Kabupaten Donggala - Ta’dung, Rensia Putri; Aziz Budianta (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
The purpose of this research is to identify the social conditions of the community and identify the economic conditions of the people in the Village Wombo Kalonggo, District Tanantovea, Kabupaten Donggala. This research applies descriptive method with survey techniques. Samples in data collection, sampling in this study was random or random sampling (Probability Sampling). The data collection technique is done by using the method of interview, observation and documentation methods. The results of this study show that the social aspects show that the social conditions of the people in the Village Wombo Kalonggo relatively homogeneous with the type of industrial society and included in the category of village communities with the level of education is still low as many as 37% of the graduates of the elementary school. While the economic conditions of the people of the Village Wombo Kalonggo included in the category of village communities with low income levels as much as 53% of people who have no income, either main income or a side.